THE EXTENT OF THE INFLUENCE OF REENGINEERING FACTORS ON THE PERFORMANCE OF ISLAMIC BANKS IN MALAYSIA FROM THE MAQASID AL-SHARIAH PERSPECTIVE - Hassan, Mohamad Ghozali; Ringim, Kabiru Jinjiri; Hasnan, Norlena; Razalli, Mohd Rizal (CENTRAL ASIA AND THE CAUCASUS, 2021)
The population of the study is the Islamic banks Headquarters (HQs) in Malaysia, sixteen (16) organizations, participating in the Islamic banking scheme (Islamic full- pledge & Islamic window of conventional bank) and registered with the Bank Negara Malaysia. In this study, the researchers distributed four (4) questionnaires for every bank, with a total of 64 questionnaires distributed to all Islamic banks HQs. The target respondents were those in top managerial level position with knowledge on the issues addressed and able to represent their organization. The sample was selected using simple random technique and data was collected by means of hand delivery using research assistants from the employees at management cadre representing their respective banks. The data was processed using Statistical Package of Social Science (SPSS), and regression analysis was conducted to test the hypothesis and determine the best BPR factors predictors of Islamic Banks performance in Malaysia. Also, factor analysis was done to reduce the dimensionality of a data set in which there are a large number of interrelated variables, while retaining as much as possible of the variation present in the data set. The result of multiple regression analysis revealed that BPR factors influence overall performance of Islamic banking in Malaysia. Also, in terms of individual BPR Factors, strategy alignment, management commitment, Information Technology (IT), investment, process redesign and less bureaucratic structure have significant impact on Islamic banking performance in Malaysia. The results indicate that all the positive factors influence the performance of Islamic banking in Malaysia, whereas other factors such as, change management, customer focus and adequate financial resources have insignificant influence on the performance Islamic banks in Malaysia. The outcome of this study provides important insights to both managers and researchers for further understanding of the effects of BPR factors on organizational performance of Islamic banks in Malaysia. It is therefore recommended that, managers should pay attention to building, re- configuring, renewing and deploying intangible resources (BPR factors), so as to deal with business environmental changes to remain efficiently and effectively profitable.